Comparing the effects of interactive and conventional video education on activation, treatment adherence, and weight changes in dialysis patients: A randomized clinical trial protocol - Sogand Sarmadi; Neda Sanaie; Akbar Zare-Kaseb (PLoS ONE, 2025)
Background Patients with end-stage renal disease undergoing hemodialysis face substantial challenges in adhering to complex therapeutic regimens, significantly impacting morbidity, mortality, and quality of life. While conventional educational methods offer some benefit, interactive digital tools may yield deeper engagement and sustained behavioral change. Objective This study assesses and compares the impact of interactive and conventional video-based education, as well as usual care, on patient activation, treatment adherence, and inter-dialytic weight gain in individuals undergoing hemodialysis. Methods A three-arm, parallel-group, randomized clinical trial will be conducted in three academic hospitals in Tehran, Iran. A sample of patients will be enrolled and distributed into one of three categories: (1) interactive video education, (2) conventional video education, or (3) typical nurse-led education. The 13-item Patient Activation Measure will be used to measure the primary outcome of patient activation. Secondary outcomes will encompass treatment adherence, as measured by the End Stage Renal Disease Adherence Questionnaire, and inter-dialytic weight gain. Evaluations will occur at baseline, immediately post-intervention, and at 1- and 3-month follow-up intervals. Data will be analyzed using intention-to-treat principles with mixed-effects modeling. Discussion This trial is among the first to rigorously compare interactive and conventional video education in a dialysis population. Findings may inform scalable, cost-effective strategies for improving self-management and adherence in patients with end-stage renal disease. This protocol was registered prospectively at ClinicalTrials.gov (Registration No. NCT07099326) on July 31, 2025. The National Research Ethics Committee also approved the study with the ethics code: IR.SBMU.PHARMACY.REC.1404.067.